36.0k views
3 votes
Solve it: f(x)= -4(x-8)^2+3

User Matchifang
by
5.5k points

1 Answer

2 votes

Answer:

x = 8 + sqrt(3)/2 or x = 8 - sqrt(3)/2

Step-by-step explanation by completing the square:

Solve for x:

3 - 4 (x - 8)^2 = 0

Subtract 3 from both sides:

-4 (x - 8)^2 = -3

Divide both sides by -4:

(x - 8)^2 = 3/4

Take the square root of both sides:

x - 8 = sqrt(3)/2 or x - 8 = -sqrt(3)/2

Add 8 to both sides:

x = 8 + sqrt(3)/2 or x - 8 = -sqrt(3)/2

Add 8 to both sides:

Answer: x = 8 + sqrt(3)/2 or x = 8 - sqrt(3)/2

User Jose Renato
by
5.1k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.